Characteristics of radar echo during AAMP98 - Hiroyuki Konishi; Makoto Wada; Masataka Shiobara (Antarctic Record, 2002)
Precipitation clouds were classified by vertical pointing radar data measured at Ny-Alesund, Arctic from December 1997 to March 1998 including the AAMP period. The results show that the apparent radar echo frequency averaged 23% over the period and increased to roughly 50% in a warmer period. The ratio of apparent time between layer and convective clouds was 64% to 36%. The propotion of layer clouds increased in the colder period and exceeded 80% in February when the averaged temperature at the ground was lower than - 20°C. The radar echo data were also compared with Micro-pulse Lidar (MPL) data during the AAMP period. The apparent MPL echo frequency reached 70%; on the other hand, that of the radar echo was 15%. The results suggest that the area of clouds was much larger than that of precipitation.